BjussuLAAO-II induces cytotoxicity and alters DNA methylation of cell-cycle genes in monocultured/co-cultured HepG2 cells - Thomazela Machado, Ana Rita; Aissa, Alexandre Ferro; Ribeiro, Diego Luis; Ferreira, Rui Seabra [UNESP]; Sampaio, Suely Vilela; Greggi Antunes, Lusania Maria (Bmc, 2019)
Background: The use of animal venoms and their toxins as material sources for biotechnological applications has received much attention from the pharmaceutical industry. L-amino acid oxidases from snake venoms (SV-LAAOs) have demonstrated innumerous biological effects and pharmacological potential against different cancer types. Hepatocellular carcinoma has increased worldwide, and the aberrant DNA methylation of liver cells is a common mechanism to promote hepatic tumorigenesis. Moreover, tumor microenvironment plays a major role in neoplastic transformation. To elucidate the molecular mechanisms responsible for the cytotoxic effects of SV-LAAO in human cancer cells, this study aimed to evaluate the cytotoxicity and the alterations in DNA methylation profiler in the promoter regions of cell-cycle genes induced by BjussuLAAO-II, an LAAO from Bothrops jaracussu venom, in human hepatocellular carcinoma (HepG2) cells in monoculture and co-culture with endothelial (HUVEC) cells. Methods: BjussuLAAO-II concentrations were 0.25, 0.50, 1.00 and 5.00 mu g/mL. Cell viability was assessed by MTT assay and DNA methylation of the promoter regions of 22 cell-cycle genes by EpiTect Methyl II PCR array. Results: BjussuLAAO-II decreased the cell viability of HepG2 cells in monoculture at all concentrations tested. In co-culture, 1.00 and 5.00 mu g/mL induced cytotoxicity (p < 0.05). BjussuLAAO-II increased the methylation of CCND1 and decreased the methylation of CDKN1A in monoculture and GADD45A in both cell-culture models (p < 0.05). Conclusion: Data showed BjussuLAAO-II induced cytotoxicity and altered DNA methylation of the promoter regions of cell-cycle genes in HepG2 cells in monoculture and co-culture models. We suggested the analysis of DNA methylation profile of GADD45A as a potential biomarker of the cell cycle effects of BjussuLAAO-II in cancer cells. The tumor microenvironment should be considered to comprise part of biotechnological strategies during the development of snake-toxin-based novel drugs.
Keywords: snake venom; epigenetics; GADD45A; CCND1; CDKN1A